Obesity: A Risk Factor of Hypertension in Adult Male Population - Asia Aziz, Misbah Ul Qamar, Nadia Tufail, Huda Abbas, Wajahat Hussain, Maria Mufti, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To determine the association between obesity and hypertension among adult male population. Study design: Cross sectional analytical Place and duration: Conducted from June 2022 to December 2022 in Medical wards of BVH, Bahawalpur. Methodology: 1124 adult male between 20-40 years of age admitted in medical wards without any illness were included. Results: Mean age of the patient was 27.1±3.6 yrs. Mostly were between the ages of 26-30 yrs i.e. 51%. Number of patients with hypertension was 19.4% and in obese persons was higher as compared to non-obese group i.e. p<0.01. Conclusion: Hypertension is higher in obese persons when comparing with non-obese subjects. Keywords: Body mass index, Adults, Hypertension